Stakeholder Pressure on MNEs and the Transfer of Socially Irresponsible Practices to Subsidiaries - Surroca, Jordi; Tribó, Josep A.; Zahra, Shaker A. (Academy of Management Journal, 2013)
In this study, we explain how multinational enterprises (MNEs) respond to pressure to conform to their stakeholders' expectations for greater attention to corporate social responsibility (CSR). We invoke institutional theory to propose that mounting stakeholder pressure in an MNE's home country leads to the transfer of socially irresponsible practices from its headquarters to its overseas subsidiaries. This transfer is more pronounced when a subsidiary is apparently unconnected to an MNE, yet is controlled by an MNE's headquarters through the appointment of the subsidiary's board members; the institutional environment of the MNE's home country enforces compliance; and the degree of institutional enforcement, vigilance, and sanctions for noncompliance in the subsidiary's host country is low. Our hypotheses are empirically supported using panel data on 269 subsidiaries in 27 countries belonging to 110 MNEs from 22 countries. Results are robust to alternative measures, explanations, and sample.